Cuba-México, una fraternidad de siglos en la historia de la Anestesiología en Latinoamérica. - Vilaplana-Santaló, Carlos Antonio (Revista Mexicana de Anestesiología)
Introduction: The administration of sulphuric ether by William Thomas Green Morton (October 16, 1846) is considered the medical breakthrough of fastest worldwide spread in history. Unfortunately, the current information available about the evolution of the specialty is still limited, particularly in Central America. Objectives: Deepen in the Anesthesiology history in Latin America. Method: Historical qualitative research where the general methods of theoretical level are used to analyze the documentary review. Results: It was on March 11th 1847 when the sulphuric ether was applied for the first time in Cuba and Latin America by the MD Vicente Antonio de Castro y Bermúdez. The news of this event constituted the first publication about anesthesia in our country. It is proved that after Cuba followed Uruguay and Brazil. It is unprecedented in the investigation the discovery of the relation between MD Sansores, from Mexico, and Cuba; through the different papers published in the Cuban Economic Repertoire of Medicine. Conclusions: In Cuba was the first time the sulphuric ether anesthesia was applied in all Latin America. Missing information in the international publications regarding the anesthesiology history in Latin America has been clarified. Through this paper work was demonstrated the links between Cuba and Mexico by the scientific production of the Mexican MD José Matilde Sansores.